2016
DOI: 10.1111/jfb.13217
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of swimming performance for fish passage of longnose dace Rhinichthys cataractae using an experimental flume

Abstract: The swimming performance of longnose dace Rhinichthys cataractae, the most widely distributed minnow (Cyprinidae) in North America, was assessed in relation to potential passage barriers. The study estimated passage success, maximum ascent distances and maximum sprint speed in an open-channel flume over a range of water velocities and temperatures (10·7, 15·3 and 19·3° C). Rhinichthys cataractae had high passage success (95%) in a 9·2 m flume section at mean test velocities of 39 and 64 cm s , but success rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…In addition, Schizothorax davidi (Sauvage 1880), Schizothorax prenanti (Tchang 1930), Schizothorax taliensis (Reqan 1907) have been listed as national class‐two protected animals and Schizothorax grahami (Reqan 1904) have been listed as Critically Endangered species in the IUCN Red List of Threatened Species (Chen & Yang, ). Fish passageways can help fishes pass dams and swimming performance of target species is important for designing passageways, whether upstream or downstream passage (Castro‐Santos, ; Katopodis & Williams, ; Dockery et al, ).…”
Section: Mean (±Sd) Critical Swimming Speed (Ucrit) and Burst Speedmentioning
confidence: 99%
“…In addition, Schizothorax davidi (Sauvage 1880), Schizothorax prenanti (Tchang 1930), Schizothorax taliensis (Reqan 1907) have been listed as national class‐two protected animals and Schizothorax grahami (Reqan 1904) have been listed as Critically Endangered species in the IUCN Red List of Threatened Species (Chen & Yang, ). Fish passageways can help fishes pass dams and swimming performance of target species is important for designing passageways, whether upstream or downstream passage (Castro‐Santos, ; Katopodis & Williams, ; Dockery et al, ).…”
Section: Mean (±Sd) Critical Swimming Speed (Ucrit) and Burst Speedmentioning
confidence: 99%
“…In this regard, some researchers have suggested that for small-sized fish, one of the main criteria for migration is the presence of low-velocity areas in the flow (Clark et al, 2014). The preference of fish for these areas is characteristic of both non-predators (Dockery et al, 2017) and predatory species (Crisp & Hurley, 1991). By the example of cyprinids, it is shown (Dockery et al, 2017) that when migrating, individuals of this family actively choose low-speed sections located along the bottom, while adhering to the station retention behaviour at higher water velocities.…”
Section: Discussionmentioning
confidence: 99%
“…The preference of fish for these areas is characteristic of both non-predators (Dockery et al, 2017) and predatory species (Crisp & Hurley, 1991). By the example of cyprinids, it is shown (Dockery et al, 2017) that when migrating, individuals of this family actively choose low-speed sections located along the bottom, while adhering to the station retention behaviour at higher water velocities. For juvenile trout, in turn, preference is given to lower flow rates compared with older individuals (Crisp & Hurley, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged speeds can be maintained for minutes to hours and use energy from both anaerobic and aerobic metabolism (Beamish 1978; Peake et al 1997). Swimming speeds vary by species and length, with larger fish typically exhibiting higher swimming speeds than smaller fish (Peake et al 1997; Aedo et al 2009; Dockery et al 2016). Vertical barriers represent an obstacle that requires a fish to jump, and they occur when the height of the structure exceeds the jumping ability of a particular fish (Kondratieff and Myrick 2006).…”
mentioning
confidence: 99%